PECTIN FROM PAPAYA PEEL - Novel Karaman, Yohandrik, L.Urip Widodo, (Jurnal Teknik Kimia, 2011)
Extraction from adhesive substance between tissue chell in the papaya peel wouldproduce a product called pectin. The aim of this research was to obtain pectin from papayapeel. Ten miligrams of papaya peel with the size of 40 mesh added with 200 ml of aquadesl,then add also HCl with various concentration: 0.01 N, 0.015 N, 0.02 N, 0.025 N, and 0.03N.The extraction was done at 80 0C temperature for: 1, 1.5, 2, 2.5 and 3 hours after that solutionextracted filtered to separate the concentrate and filtrate. The concentrate discharded and thefiltrate was pectin. Pectin filtrate then heated at temperature of 95 ° C while stirring intensivelyuntil the volume obtain half then the original volume. The filtrate cooled using acid alcohol,and stirred until evenly. After mixed evenly, filtrate left over fot about 10-14 hours. Theprecipate pectin then separated, washing with 95% neutral alcohol, and dried in an oven at 40oC for 6 hours. Dry pectin content weighed and analyzed the content of methoksil. The bestconditions result: the rendement of pectin obtained 9.2% and the content methoksil papaya peelwas 8.87% at 2 hours with the concentration of HCL 0.02 N.Keywords: extraction time, papaya peel, pectin